The Teacher’s Role in Motivating Students to Learn English in High School Level - Lena Lena; Isnaeni Wahab; Sitti Aisyah (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2024)
Creating a positive learning environment in the classroom by integrating students is crucial since learning is fundamentally about the interaction between teachers, students, and their surroundings with the goal of positive behavior changes. As a result, teachers must play a part in inspiring students to study more actively in the classroom. This research aims to determine the role of teachers in motivating student learning in English subjects. This qualitative study employed data collection techniques, including observation, interviews, and documentation. This research lasted for two months. The population in this study consisted of teachers and students of MA Bustanul Ulum Toddolimae, with the research sample consisting of one English teacher and six class X students. Thesis used qualitative data analysis techniques developed by Miles and Huberman, namely data reduction, data presentation, and concluding. The findings indicate that English teachers act as motivators, mediators, and innovators in teaching and learning activities to motivate students to participate in learning activities. This research proves that the teacher's role is very important in motivating teaching and learning activities, and the impact of providing motivation is that students feel interested and enjoy participating in English learning activities. Therefore, teachers can be said to be motivators, mediators, and innovators, while students have intrinsic and extrinsic motivation. Therefore, it is important for all educational actors, especially teachers directly involved in interacting with teachers, to help students learn in class by involving several roles that are proven to help students learn.